Financial incentives to encourage development of therapies that address unmet medical needs for nervous system disorders : workshop summary - Norris, Sheena M. Posey; Strauss, Evelyn; De Feo, Christopher Joseph; Stroud, Clare (National Academies Press, 2015)
The Institute of Medicine (IOM) Forum on Neuroscience and Nervous System Disorders, in collaboration with the IOM Forum on Drug Discovery, Development, and Translation, convened a workshop on January 20-21, 2015, to explore policy changes that might increase private sector investment in research and development innovation that fills unmet medical needs for central nervous system (CNS) disorders. Workshop participants strategized about how to incentivize companies to fortify their CNS drug development programs, shrinking obstacles that currently deter ventures. Representatives from academia, government agencies, patient groups, and industry gathered to share information and viewpoints, and to brainstorm about budget-neutral policy changes that could help widen the pipeline toward drugs that address unmet needs for CNS disorders. This report summarizes the presentations and discussion of the workshop.